Architecture, liturgy and identity : liber amicorum Paul Crossley - Opačić Zoë; Timmermann Achim (Brepols (éditions), 2011)
This collection of essays, written in honour of the eminent architectural historian Paul Crossley, brings together some of the most distinguished scholars of medieval art and architecture from the United States and many parts of Europe. Covering a broad spectrum of topics and approaches including recent discoveries, new interpretations and critical debates, this book and its counterpart Image, Memory and Devotion (also published in the Studies in Gothic Art series) offer a fitting tribute to the exceptional range of Professor Crossley s intellectual interests, while providing invaluable insights into the present study of the Middle Ages.
Keywords: Crossley Paul Mélanges et hommages; Architecture gothique Mélanges et hommages; Architecture chrétienne Europe Mélanges et hommages; Liturgie et architecture Europe Mélanges et hommages; History; Social Studies; Art History